2020
DOI: 10.1007/s42399-020-00405-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of WASH Education to Prevent Diarrhea among Children under five in a Community of Patuakhali, Bangladesh

Abstract: Diarrhea is a leading cause of death among under five children in developing countries. The burden of child diarrhea in Bangladesh is still significant. Safe water, sanitation, and hygiene (WASH) can limit the events. This study aimed to assess the effectiveness of WASH education of mothers or caregivers on child diarrhea. A community-based randomized control trial was conducted in the selected households of a rural community in Dumki Upazila, Patuakhali from March-June 2019. A total of 202 mothers/caregivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This is consistent with previous studies from Bangladesh17 that also found similar findings in relation to the regional differences in the prevalence of ARI and CDD. Begum and her colleagues also reported a higher diarrhoeal prevalence among children aged below 5 years in the similar setting and found that water, sanitation and hygiene education to the mothers was effective to reduce the burden of diarrhoea 38. According to Sarker et al 17 regions like Barisal are densely populated and is also characterised by the existence of more rivers and water reservoirs that create an enabling environment for diarrhoeal disease to spread among the population.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with previous studies from Bangladesh17 that also found similar findings in relation to the regional differences in the prevalence of ARI and CDD. Begum and her colleagues also reported a higher diarrhoeal prevalence among children aged below 5 years in the similar setting and found that water, sanitation and hygiene education to the mothers was effective to reduce the burden of diarrhoea 38. According to Sarker et al 17 regions like Barisal are densely populated and is also characterised by the existence of more rivers and water reservoirs that create an enabling environment for diarrhoeal disease to spread among the population.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with previous studies from Bangladesh [17] that also found similar ndings in relation to the regional differences in the prevalence of ARI and CDD. Begum and her colleagues also reported a higher diarrheal prevalence among children < 5 years old in the similar setting and found that water, sanitation and hygiene (WASH) education to the mothers was effective to reduce the burden of diarrhea [37]. According to Sarker et al [17], regions like Barisal are densely populated and is also characterized by the existence of more rivers and water reservoirs that create an enabling environment for diarrheal disease to spread among the population.…”
Section: Discussionmentioning
confidence: 96%
“…Researchers studied urban households' water-supply quality and in-house disinfection use [e.g. chlorine products and filters] found the prevalence of 42.2% diarrhoea among the users (Chowdhury et al 2015;Pickering et al 2019;Begum et al 2020). Sultana et al (2019) identified ARS in 5.42% of underfive children and Chowdhury et al (2020a, b) found 68% ARS-related morbidity in urban hospitals and a high ARS-related mortality rate in malnourished children.…”
Section: Living In Urban Poverty: Have-nots Child Health Hazards and Inadequate Care Servicesmentioning
confidence: 99%